Explorations of delamination and irregular structure in poly(amide-imide)-polyethersulfone dual layer hollow fiber membranes - Krantz, William B. (2013)
Dual layer hollow fiber membranes have become increasingly attractive due to their many benefits made possible by one-step fabrication using the non-solvent induced phase inversion method. Obtaining a good lamination between the two layers as well as a regular morphology are critical to make a usable hollow fiber membrane. This study aims to explore the mechanism of the lamination/delamination phenomenon and regular/irregular morphology that can occur in the fabrication of dual layer hollow fiber membrane. Simultaneous extrusion of poly(amide-imide) and polyethersulfone (PES) dope solutions was carried out by using a triple orifice spinneret. Thermodynamic properties and phase separation kinetics of the polymer dopes as well as various spinning parameters were carefully tailored in order to investigate the evolution of the membrane morphology and structure. A series of experiments have confirmed that when the external coagulant, water, has a higher diffusion rate in the outer layer than in the inner layer, the outer layer tends to expand to form large macrovoids and to hold more water at the interface. As a result, the accumulated water probably impedes the adhesion of the two layers, leading to a delamination of two layers. On the other hand, if water has a slower penetration rate through the outer layer dope than the inner layer dope, a good adhesion between these two layers is expected. Under this scenario, since macrovoids formed in the inner layer may lead to the expansion of the inner layer, a distortion of the finger-like structure/macrovoids in the inner and an irregularity of the inner contour may occur. This study provides a solid foundation to develop superior dual layer hollow fiber membranes with an inter-penetrating dual layer structure.